Evaluation of the Quality of Ethiopian Journal of Reproductive Health - Teklu, Alula; Ashenafi, Wondimye; N Haregu, Tilahun; Banko, Muhdin Abdo (Ethiopian Journal of Reproductive Health, 2023)
Introduction: The Ethiopian Journal of Reproductive Health (EJRH) is a local journal that has been published by the Ethiopian Society of Obstetrics and Gynecology (ESOG) for over 10 years. The objective of this study was to examine the quality of the journal. Methods: A mixed-methods approach that employed reviews of published editions of the journal, key informant interviews of those who have roles in the management of the journal, researchers who have the experience of publishing in EJRH and other journals, and editors-in-chief of other journals was conducted. Self-appraisal of the journal using a standard checklist and office visits to assess staffing, infrastructure, manuscript follow-up, and coordination were also conducted. In addition, an online survey questionnaire was administered to assess perception and use of the EJRH by members of ESOG. Results: There have been nine issues with four to six articles per issue in the last 10 years. This was a 30% performance against the target. The total number of issues was lower than average when compared to other local journals. Seven out of the nine issues of EJRH were available online. The journal has no online submission system and was yet to be indexed. The journal scored low in 19 of the 20 self-appraisal criteria. The majority of ESOG members knew about EJRH, but only 10% had a publication in the journal. Findings suggest that there are critical areas that need improvement for the journal to be reputable and influential. Conclusion: A substantial reform with focus on having a fully functional editorial team, a web-based submission and peer review process, a well-equipped editorial office, and human resources were needed. Benchmarking experiences from other journals and adopting standard operating procedures were recommended. Strengthening collaboration with universities and research institutions will also be critical.